Examining exclusionary impact of blair toilets on learners with disabilities in rural primary schools, Zimbabwe - Chidarikire, Munyaradzi; Chidarikire, Jane Nyokanhete (African Perspectives of Research in Teaching & Learning (APORTAL), 2024)
This qualitative research paper examines the exclusionary impact of Blair toilets on learners with disabilities in rural primary schools in Zimbabwe. By identifying the challenges faced by these learners, such as the tragic loss of life due to falling into Blair toilets' pits, the study underscores the urgent need to address this issue. The Social Model of Disability provides a theoretical framework that can be used to understand and analyse the exclusionary impact of Blair toilets on learners with disabilities in rural primary schools in Zimbabwe. The study involved fifteen participants who were purposively selected based on criteria such as gender and personal experiences. Data was collected through focus group discussions and analysed using content thematic analysis. The study found that the exclusion of learners with disabilities from learning environments is due to the lack of accessible Blair toilets. Consequently, some learners with disabilities are forced to drop out of school due to the inaccessible nature of the toilets, which hampers their ability to attend classes regularly. Based on this finding, the article recommends that the government and other stakeholders should work together to construct Blair toilets that are accessible and user-friendly for learners with disabilities. This may involve building flush toilets and utilizing resources such as bricks and solar-powered boreholes to ensure an adequate water supply.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 2, Volume 8, 2024
Keywords: Blair toilets; Exclusion; Learners with disabilities; Quality education; Rural primary schools; Zimbabwe; Inclusive education -- Zimbabwe; Education, Primary -- Zimbabwe; Total quality management in education; People with disabilities; Rural schools -- Zimbabwe; Toilets